2015
DOI: 10.1016/j.tcs.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent semantics, generalized compositionality and analytic classic-like tableaux for finite-valued logics

Abstract: The paper is a contribution both to the theoretical foundations and to the actual construction of efficient automatizable proof procedures for non-classical logics. We focus here on the case of finite-valued logics, and exhibit: (i) a mechanism for producing a classic-like description of them in terms of an effective variety of bivalent semantics; (ii) a mechanism for extracting, from the bivalent semantics so obtained, uniform (classically-labeled) cut-free standard analytic tableaux with possibly branching i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…It may be observed that: (i) agents may not be aware even of easy consequences of their assumptions and there is still a difference between implicit and explicit information, 11 (ii) even implicit information that can be feasibly extracted from the explicit one requires the consumption of resources. Both observations raise interesting questions that we do not address here.…”
Section: Among Others)mentioning
confidence: 99%
See 1 more Smart Citation
“…It may be observed that: (i) agents may not be aware even of easy consequences of their assumptions and there is still a difference between implicit and explicit information, 11 (ii) even implicit information that can be feasibly extracted from the explicit one requires the consumption of resources. Both observations raise interesting questions that we do not address here.…”
Section: Among Others)mentioning
confidence: 99%
“…We shall 11 This issue is interestingly related to the vast literature on awareness (see, for example, [42,30,41,49]). 12 In fact, in this context, the signs "T " and "F " act as propositional attitudes and, in a multiagent setting, can be indexed by symbols "x, y, z, ..." standing for different agents.…”
Section: Among Others)mentioning
confidence: 99%
“…As a practical application of that idea, the Suszko Reduction, seen as the technical counterpart of Suszko's Thesis, has nowadays been given a fully algorithmic implementation that applies to any finite-valued logic, and this has been used to provide uniform classic-like analytic deductive counterparts to all such logics (cf. [5]).…”
Section: Introductionmentioning
confidence: 99%
“…We do not present actual Suszko reductions of specific logics for that matter, but mostly use the notion toward irreducibility arguments. In that regard, our perspective differs from the important work of Caleiro and Marcos (2012) and Caleiro et al (2015), who propose a constructive method to compute Suszko reductions from arbitrary semantics. Their approach is in a sense more general, because it is not restricted to logics for which the reduction preserves truth-functionality, and it is output-oriented.…”
Section: Ranks and Truth-functional Reductionmentioning
confidence: 90%
“…Suszko gave a precise answer to that problem for a large class of consequence relations. He proved that every Tarskian relation, namely every reflexive, monotonic, and transitive consequence relation, can be characterized by a class of two-valued models (Caleiro and Marcos, 2012;Caleiro et al, 2015;Suszko, 1977;Tsuji, 1998;Wansing and Shramko, 2008). Suszko's problem and his result are of fundamental importance to understand the role and nature of truth values in logic.…”
Section: Suszko's Problemmentioning
confidence: 99%